Pengembangan Buku Keanekaragaman Anggrek (Orchidaceae) Berbasis Literasi Sebagai Sumber Belajar - Rifka Febrianti; Tri Harsono; Syahmi Edi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to analyze the supplementary books used by Biology/Biology Education students at Universitas Negeri Medan (Unimed), to assess the feasibility of literacy-based supplementary books, and to determine the differences in learning outcomes of students taking the Spermatophyta Taxonomy course after using the literacy-based supplementary book in the Biology Department of Unimed. The method used is research and development (R&D) employing the Thiagarajan model, which consists of four stages: 1) define, based on a needs analysis showing that 60% of students agreed on the development of a literacy-based book on orchid (Orchidaceae) diversity; 2) design, in which the book was developed based on four aspects of scientific literacy: (a) science as a body of knowledge, (b) science as a way of investigating, (c) science as a way of thinking, and (d) the interaction of science, technology, and society; 3) development, where orchid observation was conducted at the Pane Anggek orchid garden, involving four types of orchids: dendrobium, moon orchid (phalaenopsis), cattleya, and ground orchid; 4) dissemination, involving product trials with both small and large groups of students. The results show that the material expert validation score was 80% (good category), the scientific literacy aspect scored 81% (good), the learning expert gave a score of 87.9% (very good), and the Layout design expert gave a score of 85.5% (very good). Product trials with small student groups resulted in a score of 87% (very good), while trials with large groups yielded a score of 89% (very good). The N-gain test showed the developed book was moderately effective for use in the Spermatophyta Taxonomy course with a score of 63% (moderately effective). The t-test results from pretest and posttest scores showed a value of (Sig. 2-tailed) = 0.000 < 0.05, indicating a significant difference in students’ cognitive outcomes between pretest and posttest. The conclusion of this study is that the literacy-based orchid (Orchidaceae) diversity book as a learning resource can improve students’ cognitive abilities.   Keywords: Development, Literacy, Orchid, Supplementary Book